Nota dos editores - Santos, Raimundo Nonato Silva; Freire, Luciano Nunes Maia; Machado, Raquel Cavalcanti Ramos (Suffragium - Revista Científica do Tribunal Regional Eleitoral do Ceará, 2024)
Nota dos editores